Maximizing The Use of "Speed Up English 6" Textbook Through Contextual Teaching and Learning - Munir, Munir; Patak, Andi Anto (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The objective of this research is to find out the strengths and the weaknesses of the use of "Speed Up English 6" textbook through contextual teaching and learning of the sixth grade students of SDN IKIP I Makassar. This research employed a descriptive method. The data source was "Speed Up English 6" as the reference book of the sixth grade students of SDN IKIP I Makassar. It was written by Rita Kurniawan and Naning Partini, and published by Yudhistira in 2006. The informants were 10 students of class 6' and 10 students of class 6. The collected data were analyzed by using percentage descriptive analysis. The result of this research showed that (1) the strengths of this textbook lay on its colorfulness either its cover or contents and its pictures which are related to the real world as well as provide syllabus based on standardized national curriculum, (2) the weaknesses of this textbook lay on some activities which are not related to the syllabus, and (3) this research found that Contextual Teaching and Learning contribute to maximize the use of "Speed Up English 6" textbook.Key words: Speed up English 6, textbook, contextual teaching and learning.